Effects of Paljeongsan-gamibang on the damage of Rat Kidney induced by Glycerol - Wang-Su Yun; Kyung-Son Soh; Chan-Gil Jeong (Korean Pharmacopuncture Institute, 2007)
Objective : We performed this study in order to investigate the effects of Paljeongsan-gamibang(八正散加味方) on the renal failure. Methods : We injected 8ml/kg of 50% glycerol on the rats. And then administered Paljeongsan-gamibang extract ; 209mg/200g/day to sample group during 3 days and observed the body temperature, urine volume, stool volume and the levels of creatinine, glucose, inorganic phosphorus, Na+, K+, Cl-, threonine, tyrosine in blood and creatinine, glucose, threonine, tyrosine in urine. Results : 1, The sample group administered Paljeongsan-gamibang showed a suppressive effect of body temperature, an improving effect in capability of concentrating urine at convoluted tubule and showed an increasing effect of stool volume. 2. The sample group administered Paljeongsan-gamibang showed a lowering effect in creatinine level in blood and showed an increasing effect in the levels of inorganic phosphorus, Na+, K+, Cl-, threonine and tyrosine in blood. 3. The sample group administered Paljeongsan-gamibang showed an increasing effect in creatinine level in urine and showed a lowering effect in the levels of glucose, inorganic phosphorus, threonine and tyrosine in urine. Conclusions : Conclusively, Paljeongsan-gamibang was recognized to have a curative effect against the damage of rat kidney induced by 50% glycerol, especially to improve the capability of reabsorption in proximal convoluted tubule.